Telling the truth in economic theory - Meeks, Jaqueline Gay (The University of Edinburgh, 1975)
Need a theory's assumptions be true? In a since notorious essay, the economist Friedman argued they need not be and in abstract theories often won't be. The first part of the thesis discusses his case, which has been widely misunderstood,. It concludes that, whilst false assumptions may fulfil the role of epitomising and implying truth, those in Friedman's key economic example do not. The rest of the thesis then relates Friedman's case to that in defence of general equilibrium theory (the heart of orthodox economic theory) and argues that this defence fails. Two complementary arguments against the defenders' position are presented, the first working from the fact that the theory's assumptions are not true and the second considering what would happen if they were - the conclusion being that the theory relates neither to actual cases nor to possible polar ones. Comparisons drawn with rival economic theories end this case-study in the philosophy of economics.